Failure modes and behaviour of stiffened engineered timber wall systems under axial-loading. (June 2020) - Orlowski, Kristopher
Abstract: With automated prefabrication on the rise and sustainability principles becoming more prevalent in buildings, a novel material efficient stiffened engineered timber wall system has been developed. Lightweight timber framing is limited to only a few stories and although Cross-Laminated Timber (CLT) structures have been recently used in taller wooden buildings, they are material inefficient against buckling due to their basic monolithic design. A novel material efficient prefabricated stiffened engineered timber wall system is proposed as an intermediary solution. This fully prefabricated panelised system was designed and manufactured to typical conditions with the aid of an industry partner. Experimental axial load testing was conducted, with the stiffened engineered timber walls in various structural configurations to robustly understand its performance under various design scenarios. Areas of particular focus were the serviceability load, ultimate capacity, out-of-plane deflection and failure modes. The key findings around these have been presented along with the behavioural and performance response to alternative loading conditions, height of wall and manner of connection between the key components.